Sustainable Development and Sovereign Debt: A Legal Perspective on Debt Sustainability for Africa - Nattabi, Patricia Kirumira (East African Nature and Science Organization, 2025)
The World Bank’s 2023 Debt Sustainability Analysis (DSA) puts twelve low-income countries (LICs) in Africa at a high risk of debt distress while six are in debt distress. The recurring unsustainable debt in Sub-Saharan Africa has had a long-standing effect on the pace of development, as measures taken to accommodate debt resolution have often had a counter-effect on economic performance, as investment in development priorities and the social welfare of citizens have often taken a back seat to debt servicing. The United Nations 2030 Sustainable Development Agenda and its implementation Action plans address unsustainable debt as a major obstacle to achieving sustainable development and therefore highlight the importance of supporting poverty eradication by filling the financial gap and encouraging coordinated assistance in developing countries to attain long-term debt sustainability through relief, restructuring, and financing. However, there is a need to clarify the norms underlying sustainability principles and ground them in law to create stronger frameworks for certainty, legitimacy, and effectiveness in their application to Africa’s sovereign debt problems. This research analyses the arguments for a sustainable development approach to improving debt sustainability in Africa, by relating the state responsibilities and obligations within the sustainable development norms in international law and those responsibilities accruing to creditors and sovereign debtors. It analyses these aspects with three emergent norms of international law, sustainable development, shared responsibility, and debt sustainability, and provides a correlation with the socio-economic, environmental, and governance dimensions of sustainable development. The research finds that neglecting the coherence of these aspects in African debt strategies not only increases vulnerability for debt crisis but also prolongs recovery, thereby slowing the progress towards sustainable development.